The Anti‐Inflammatory Impact of Omega‐3 Polyunsaturated Fatty Acids During the Establishment of Endometriosis‐Like Lesions. (5th June 2014) - Attaman, Jill A.; Stanic, Aleksandar K.; Kim, Minji; Lynch, Maureen P.; Rueda, Bo R.; Styer, Aaron K.
<x xml:space="preserve">Abstract</x> Problem The anti‐inflammatory impact of three polyunsaturated fatty acids (3‐PUFA) in endometriosis is incompletely understood. The effect of 3‐PUFA on endometriosis‐like lesions is evaluated as a potential anti‐inflammatory treatment target. Method of Study Wild Type (WT) and transgenic Fat‐1 mice (high levels of endogenous 3‐PUFA) were utilized in a uterine tissue transplant endometriosis model. Experimental donor × host pairs included: WT × WT (WW), WT × Fat‐1 (WF), and Fat‐1 × Fat‐1 (FF). Cytokine content (IL‐1β, IL‐2, IL‐4, IL‐6, IL‐10, IL‐12, IL‐17A, IFN‐γ, TNF‐γ, MCP‐1 and RANTES) and immunocellular composition in lesions was determined. Results Intralesion IL‐6 in WF hosts was 99‐fold lower than WW hosts (P = 0.03). Compared to WW host lesions, Cox‐2 levels were decreased in WF [1.5‐fold (P = 0.02)] and FF [1.2‐fold (P = 0.01)] host lesions, respectively, and intralesion VEGF expression was increased [1.8‐fold; P = 0.02 (WF) and 1.5‐fold; P = 0.01 (FF)]. Lesions in FF hosts demonstrated reduced phosphohistone 3 expression (70%; P = 0.03) compared to WW control hosts. Conclusions Systemic host 3‐PUFA levels influence immune, angiogenic, and proliferative factors implicated in the early establishment of endometriosis.